Money as a social technology - Grébel, Szabolcs (Public Finance Quarterly, 2024)
Peet van Biljon and Alexandra Reed Lajoux’s Money Creation: the past and present of society’s most important technology will be published in English in 2020, and its Hungarian translation was published by Pallas Athéné Könyvkiadó, also in 2020.